Differential expression and interaction of melatonin and thyroid hormone receptors with estrogen receptor α improve ovarian functions in letrozole-induced rat polycystic ovary syndrome - Ghosh, Hindole (2022)
Fil: Ghosh, Hindole. Kalinga University. Department of Zoology; India